2022
DOI: 10.12998/wjcc.v10.i16.5287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery strategy to shorten perioperative fasting in children undergoing non-gastrointestinal surgery: A prospective study

Abstract: BACKGROUND Enhanced recovery after surgery strategies are increasingly implemented to improve the management of surgical patients. AIM To evaluate the effects of new perioperative fasting protocols in children ≥ 3 mo of age undergoing non-gastrointestinal surgery. METHODS This prospective pilot study included children ≥ 3 mo of age undergoing non-gastrointestinal surgery at the Children’s Hospital (Zhejiang University School of Medicine) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…This research ensured regular surveillance of surgical schedules, pinpointing and mitigating potential delays to avert extended fasting. The authors accentuated the paramountcy of not just introducing a revised fasting protocol but also the thorough training of the medical staff to adeptly apply it, especially given the frequent surgical rescheduling [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research ensured regular surveillance of surgical schedules, pinpointing and mitigating potential delays to avert extended fasting. The authors accentuated the paramountcy of not just introducing a revised fasting protocol but also the thorough training of the medical staff to adeptly apply it, especially given the frequent surgical rescheduling [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 270 patients, those reminded via text message fast showed a shorter average liquid fasting time (3.5 vs. 6.5 h, p < 0.0001), but solid food fasting remained unchanged. Some patients' reluctance to eat late also potentially influenced fasting periods [4,18,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the updated 2023 ASA guidelines on fasting, include the use of oral midazolam, it is recommended to minimize fasting duration in children. Therefore, every effort should be made to permit clear liquids in healthy children up to 2 h before medical procedures ( 113 ), and that early eating is safe as long as the patients have recovered from anesthesia and swallowing function evaluation is done ( 114 ). It’s important to note that following the ASA fasting guidelines is recommended for patients undergoing moderate sedation, where the child may not be able to maintain verbal contact or may undergo deep sedation.…”
Section: Fastingmentioning
confidence: 99%
“…Desde então, o conceito tradicional de jejum e privação de água tem sido questionado por anestesistas e cirurgiões após anos de prática. Atualmente, a Sociedade Americana de Anestesiologistas (ASA) e a ERAS Society apresentaram suas opiniões orientadoras, porém nenhum consenso foi alcançado 2 .…”
Section: Introductionunclassified